Membangun Pembaca Tangguh: Strategi Guru dalam Mengatasi Kesulitan Membaca di SD - Ni’matul Tri Maulidiyah; Ellen Muznatin Nisa; Silvia Cantika Putri; Jenita Cintia Wardani; Nia Altiara; Vivi Rulviana (Prosiding Konferensi Ilmiah Dasar, 2026)
Reading is a fundamental skill essential for elementary school students as it serves as the foundation for understanding various subjects. However, many students still experience reading difficulties due to internal and external factors. This study aims to analyze various strategies implemented by teachers to address reading difficulties in elementary school students through a literature review. The study used a descriptive qualitative approach with a literature review method. Data sources consisted of scientific articles published between 2021 and 2026, obtained from Google Scholar, Garuda, SINTA, and relevant international journals. The data were analyzed using content analysis techniques to identify, categorize, and synthesize the various strategies used by teachers. The results showed that effective strategies included intensive mentoring, gradual reading practice, the use of learning media such as letter cards and visual media, the application of phonics methods, the provision of reading corners, remedial learning, additional study hours, and collaboration with parents. These strategies have been proven to improve students' reading abilities, motivation, and self-confidence. Therefore, implementing strategies tailored to students' needs and supported by collaboration between schools and parents is key to overcoming reading difficulties in elementary schools.